A comparative study of topical 5% tranexamic acid and triple combination therapy for the treatment of melasma in Indian population - Sandeep Khuraiya; Dilip Kachhawa; Bharti Chouhan; Mitali Dua; Pankaj Rao (Wolters Kluwer Medknow Publications, 2019)
Introduction Melasma is an acquired hyperpigmentary disorder and poses great therapeutic challenge and has a high recurrence rate. Topical 5% tranexamic acid (TA) is a novel and safe alternative therapy for melasma. The aim of our study was to evaluate the efficacy of topical solution of 5% TA and compare it with triple combination therapy (hydroquinone, tretinoin, fluocinolone) in Indian population. Materials and Methods This was a prospective comparative study of 12 weeks. A total number of 25 patients between 18 and 50 years of age were included in the study. Patient's face was divided into two halves (split face), and on one half of the face (i.e., on left), topical 5% TA and on the other half of the face (i.e., on right), topical triple combination therapy were applied. The melasma area severity index (MASI) and side effects were evaluated at baseline and every 15 days. Photographs were taken at alternate visits (i.e., 30 days) and compared with earlier one by an independent observer. Results The study was completed on 23 patients. The mean MASI scores decreased significantly in both the groups (P < 0.05), but there was no significant difference between them (P > 0.05). However, the side effects of triple combination therapy were significant compared with TA. At the end of 12 weeks, in group 1, photographic evaluation showed excellent response in 26%, good response in 60.1%, fair response in 8.6%, and poor response in 4.3%. In group 2, there was excellent response in 34.7%, good response in 56.5%, fair response in 4.3%, and poor response in 4.3%. Conclusion This study revealed that the topical 5% TA is a safe effective, and better alternative with good patient acceptance for the treatment of melasma. The study revealed improved pigmentation in both tested sides, but topical 5% TA has less side effects such as erythema, irritation, and telangiectasia as compared to triple combination.